The Problematics of Arabic Language Learning at Islamic Boarding School - Yasin, Agus; Fadhlullah, Muhamad (Study Program of Arabic Language Teaching, 2025)
This study aims to identify and analyze the challenges in Arabic language learning at Subulussalam Islamic Boarding School Kresek, Tangerang. Although Arabic is one of the core subjects taught intensively at the school, various obstacles in the learning process are still frequently encountered by both students and teachers. This study carefully examines these challenges and explores appropriate solutions to enhance the overall effectiveness of Arabic language teaching at the school. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving dedicated teachers and students actively engaged in Arabic language learning at Subulussalam Islamic Boarding School Kresek. The study population comprises 50 teachers and 200 students participating in Arabic language programs. A purposive sampling technique was used, selecting 5 teachers and 15 students from various class levels as research samples. The collected data were comprehensively analyzed using qualitative descriptive analysis to identify key issues and explore applicable solutions within the broader context of Arabic language learning. The findings indicate that the primary challenges include limited teaching materials, insufficient language interaction in learning, and a misalignment between teaching methods and students' needs.